If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3h + 2 = 8 Reorder the terms: 2 + -3h = 8 Solving 2 + -3h = 8 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3h = 8 + -2 Combine like terms: 2 + -2 = 0 0 + -3h = 8 + -2 -3h = 8 + -2 Combine like terms: 8 + -2 = 6 -3h = 6 Divide each side by '-3'. h = -2 Simplifying h = -2
| 17j-17j+j=16 | | 3p+2-1=-2 | | -6u-26=2(u-5) | | X-5=w | | -4q-(-18q)=-14 | | 4b+4b-7=25 | | 6a-1=2 | | 12=3(7-2) | | 2x-2x+2x+4x-5x=4 | | 4x+.5(8x-6)=2(4x+3) | | 0=12b-12 | | -5j+-16j+13j=16 | | 12=3(-2-2) | | h^2+b^2=8.5-h^2 | | x^2+y^2=8.5-h^2 | | 2c-(-6)=12 | | 5x-1+1x+15=6+5x+14-2x | | b+9=8+7 | | -6x-6(-3x)=-24 | | 2y+11=6-y | | (3k+1)x^2+2x=1 | | 7v+2(v-2)=-22 | | t*5-7=10 | | -5(2r+4)=10 | | -9x+-20x+19x+5x-(-9x)=-12 | | -6x+4x=14 | | 6t-3t-3t+3t=18 | | x*(x+1)+109=x+(x+1) | | 16t-15t=14 | | x=y-11 | | -3x-(-8x)=15 | | (8/125)-2/3 |